2001
DOI: 10.1507/endocrj.48.723
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Promoter Region of the Glucocorticoid Receptor Gene Is Associated with Its Transcriptional Activity.

Abstract: Abstract.Since glucocorticoid exerts its biological effects by binding to its receptor, the expression efficiency of the glucocorticoid receptor (GR) gene could influence glucocorticoid sensitivity.We found a polymorphism of cytosine/adenine (-22 C/A) in the upstream region of the OR gene. There was no difference in the allelic frequency between normal and type 2 diabetic subjects. The promoter activity determined by luciferase assay was significantly lower in the -22 A allele than in the -22 C allele in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The most common NR3C1 polymorphism studied in a wide variety of diseases is N363S. One polymorphism has been reported in the promoter region of the NR3C1 gene and is associated with decreased transcription of the gene [Ikeda et al, 2001]. Two silent polymorphisms (D678D and N766N) are found in the ligand-binding domain.…”
Section: Variations In the Glucocorticoid Receptor Genementioning
confidence: 99%
“…The most common NR3C1 polymorphism studied in a wide variety of diseases is N363S. One polymorphism has been reported in the promoter region of the NR3C1 gene and is associated with decreased transcription of the gene [Ikeda et al, 2001]. Two silent polymorphisms (D678D and N766N) are found in the ligand-binding domain.…”
Section: Variations In the Glucocorticoid Receptor Genementioning
confidence: 99%
“…Thus, results from one population do not necessarily apply to others. For example, the N363S polymorphism has been reported in Australia with an allele frequency of 7.4% (Lin et al, 1999), whereas in two Asian studies (Ikeda et al, 2001;Lei et al, 2003), no N363S carriers were found. Effects of polymorphisms may differ between races, due to different combinations of polymorphisms of several genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, no association was found with hypertension or type 2 diabetes. Interestingly, in a Japanese as well as in a Chinese population, the N363S variant did not occur (Ikeda et al, 2001;Lei et al, 2003). , who had higher cortisol levels after 1-mg DEX and a smaller decrease in cortisol, which suggests that the ER22/23EK variant is associated with a relative resistance to GCs.…”
Section: The N363s Polymorphism Of the Gr Genementioning
confidence: 97%
“…Exclusion criteria were: (1) concurrent illnesses such as severe heart disease, renal disease, and liver disease; (2) nausea and/or vomiting prior to treatment; (3) illnesses from which nausea and/or vomiting were a result, e.g., bowel obstruction, and peptic ulcer; (4) performance status (PS) of 4; (5) past history of hypersensitivity to drugs; (6) currently taking other antiemetic drugs and/or antipsychotic medication; (7) pregnant or possibly pregnant; and (8) deemed unsuitable by a doctor. In addition, patients who underwent radiation therapy or who experienced brain metastasis during the course of the trial were handled separately at the time of data analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…Secondly, some differences may be seen in the metabolism of steroids between ethnic groups. [4][5][6][7] As steroids are not indicated for antiemetic control in Japan, insuffi cient data are currently available related to their optimal dosing. This study was conducted to measure the optimal dose of dexamethasone, in combination with the 5-HT 3 receptor antagonist granisetron, for antiemetic therapy during CDDP-containing chemotherapy for head and neck cancer in a Japanese patient population.…”
Section: Introductionmentioning
confidence: 99%